Combined forecasts used to improve the performance of unemployment rate forecasts in Romania - Bratu, Mihaela (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2015)
The main goals of this research are: the evaluation of unemployment rate forecasts made for Romania by three experts in forecasting for 2001-2011 (E1, E2 and E3) and the proposal of some combined forecasts to improve the predictions performance. The predictions are made at the same time. The forecasts performance implies three directions: accuracy, biasedness and efficiency. In addition to the usual accuracy indicators, multi-criteria ranking methods were used to make a hierarchy of experts according to the forecasts accuracy and the forecasts overall performance, resulting in the following classification: E3, E1 and E2. Besides the combined forecasts based on three classical schemes (optimal scheme, equally-weighted scheme, inverse MSE weighting scheme), the combined predictions proposed by us based on mean error, improved the performance, solving in most of the cases the biasness problem and generating more accurate and efficient forecasts.
Argumenta Oeconomica, 2015, Nr 1 (34), s. 99-125
Keywords: forecasts; predictions; performance; accuracy; bias; efficiency; multi-criteria ranking methods; combined forecasts